Digital Watermarking For Images - Aileen Koay, Yee Hoon (Universiti Sains Malaysia, 2006)
The success of the Internet allows for the prevalent distribution of multimedia data easily. Meanwhile, the ease of reproduction and distribution of digital documents create problems for authorized parties that wish to prevent illegal use of such documents. To solve this problem, a digital watermarking method for copyright protection is introduced. In this dissertation, a color image watermarking system for copyright protection is proposed. A visually recognizable watermark is used and embedded in the wavelet decomposition of the color host image. The wavelet decomposition of host image used in this project is Stationary Wavelet Transform (SWT) level 1 and level 2. In order to identify the suitable channel of RGB color model for watermarking, three different channels of RGB color model are tested by using different host images and watermarks. The experimental results show that the proposed watermarking scheme is robust to Gaussian filtering, Gaussian noise, salt and pepper noise, speckle noise and JPEG compression.